Learning Cycle Model Assisted Audio Visual Increase Science Knowledge Competence - Purnamaningsih, I Gusti Ayu Ita; Semara Putra, DB. KT. Ngr; Wiarta, I Wayan (International Journal of Elementary Education, 2020)
The low ability of science knowledge competence was caused by less optimal use of innovative learning models and the lack of using instructional media. This study aimed to analyze the significant effect of the learning cycle model assisted by audiovisual media on the IPA knowledge competence of the fourth-grade students. The type of this study was a quasi-experimental research with the non-equivalent control group design. The samples in this study were determined using the Cluster Random Sampling technique where by fourth-grade with 30 students as an experimental group and fourth-grade with 31 students as a control group. The population in this study was all students in grade IV elementary school which has 257 students.Â  The data of science knowledge competence were collected using the test method and the instrument used was an ordinary multiple-choice objective. The data were analyzed using a t-test. Based on the result of data analysis, the score of tcount=3,184 while at the significant level 5% and dk = 59 ttable=2,045 so that tcount=3,184 > ttable = 2,045. Based on the testing criteria, then Ho was rejected and ð»ð‘Ž was accepted. There were significant differences in the science knowledge competence between the group control and the experimental group. The average of science knowledge competence students in the experimental group and control group was 85,677 > 70, 935. It can be concluded that the Learning Cycle model assisted by audiovisual media influences the science knowledge competence in the fourth-grade students of elementary school.